Cover Image. (3rd July 2020) - Liu, Zhen; Ming, Weihua; Du, Zuolei; Zhou, Cuiying
Abstract : The cover image is based on the Research Article Precise integration method for solving the seepage‐stress coupling problem in rock mass with singular possibilities of the coupling matrix by Zhen Liu et al., https://doi.org/10.1002/nag.3083 .